2011
DOI: 10.1097/tp.0b013e3182298a15
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disc Repair by Autologous Mesenchymal Bone Marrow Cells: A Pilot Study

Abstract: MSC therapy may be a valid alternative treatment for chronic back pain caused by degenerative disc disease. Advantages over current gold standards include simpler and more conservative intervention without surgery, preservation of normal biomechanics, and same or better pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
414
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(429 citation statements)
references
References 32 publications
13
414
0
2
Order By: Relevance
“…To assess whether continuous culture can produce clinically relevant populations of NP cells, cell doubling was calculated. Similar population doubling was found using both methods and both total cell counts were suitable for clinical applications (Mochida et al, 2015;Orozco et al, 2011) (Fig. 3B).…”
Section: Continuous Expansion Culture Preserved Gene Expression Of Ecsupporting
confidence: 51%
See 1 more Smart Citation
“…To assess whether continuous culture can produce clinically relevant populations of NP cells, cell doubling was calculated. Similar population doubling was found using both methods and both total cell counts were suitable for clinical applications (Mochida et al, 2015;Orozco et al, 2011) (Fig. 3B).…”
Section: Continuous Expansion Culture Preserved Gene Expression Of Ecsupporting
confidence: 51%
“…Autologous chondrocyte implantation has had some success at repairing focal cartilage defects in patients (Brittberg et al, 1994;Brittberg et al, 2001). Autologous stem cell implantation for IVD repair has shown some clinical promise (Orozco et al, 2011). Autologous NP implantation has been shown to be safe and not cause low back pain, yet NP cells insufficiently repair IVDs (Mochida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the use of growth factors, gene and stem cell therapies, and tissue engineering strategies might be feasible and effective approaches to prevent and treat IDD [1]. Indeed, very recently bone marrow mesenchymal stem cells have been used in a clinical phase I study in patients seeking BP with moderate IDD, showing safety and pain improvement [2]. However, several unsolved issues are still present in the translation of this new cell therapy to the clinic, such as the most reliable transplantation method, including the surgical route to approach the disc, and suitable animal models to test regenerative techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns regarding an immune reaction to allogenic stem cells in humans have limited the utilization of such cells in clinical trials. Orozco et al [62] transplanted autologous MSCs into ten patients diagnosed with Degenerative Disk Disease [62] . They found improvements in pain and disability within three months of treatment.…”
Section: Disc Regenerationmentioning
confidence: 99%